2021
DOI: 10.1590/1980-549720210006.supl.2
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco use, cessation, secondhand smoke and exposure to media about tobacco in Brazil: results of the National Health Survey 2013 and 2019

Abstract: Objective: To compare indicators of tobacco use, secondhand smoke, cessation and exposure to pro- and anti-tobacco media in 2013 and 2019, and to describe these indicators according to sociodemographic variables in 2019. Methods: Cross-sectional study with data from the National Health Survey. The indicators of use, secondhand smoke, cessation and exposure to tobacco-related media were evaluated. Prevalence and confidence intervals (95%CI) were estimated for the total population in 2013 and 2019 and according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
1
6
1
Order By: Relevance
“…Geographic disparities reflect variations in cigarette prices and smoking prevalence across Brazilian states and are worthy of analysis. 8 , 16 The study tells the history of smoking behaviors in Brazil but does not identify which factors led to observed changes. Other research methods should ascertain the effects of policy changes on the trends revealed by this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Geographic disparities reflect variations in cigarette prices and smoking prevalence across Brazilian states and are worthy of analysis. 8 , 16 The study tells the history of smoking behaviors in Brazil but does not identify which factors led to observed changes. Other research methods should ascertain the effects of policy changes on the trends revealed by this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, cigarette smoking remains the dominant form of combustible tobacco used in Brazil representing 97.6% of overall smoking prevalence in 2019. 8 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are also consistent with reports that 80% of all current smokers live in low- and middle-income countries. Socioeconomic inequalities were also observed within countries towards more socially vulnerable individuals regarding smoking 23 and physical inactivity 24 , possibly due to a lack of resources, social support, and motivation to modify harmful behaviors 24 and higher multimorbidity prevalence. However, behavioral determinants might be modifiable by public policies, and interventions encouraging better lifestyle choices have been reported with a 70% rate of success 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The independent variables included were: sociodemographics [sex, age group ( 34 ), self-declared race/skin color ( 35 ), education ( 36 ), living with a spouse/partner, geographic region ( 37 ), and area of residence ( 37 )]; lifestyle [tobacco use ( 38 ), alcohol abuse ( 39 ), leisure-time physical activity ( 40 ), recommended consumption of fruits and vegetables ( 41 ), ultra-processed food consumption ( 41 ), regular consumption of soft drinks or artificial juices ( 41 ), and nutritional status ( 42 )]. Questions, answer options, operational definitions and, analysis categories are in Supplementary Table S2 .…”
Section: Methodsmentioning
confidence: 99%